ANALISIS KETERSEDIAAN DAN JANGKAUAN FASILITAS PENDIDIKAN SMA UNTUK PENINGKATAN PELAYANAN PENDIDIKAN DI KABUPATEN SUMEDANG - Fanesya Noer Salsabila; Lili Somantri; Iwan Setiawan (JURNAL GEOGRAFI, 2021)
Availability and equalizing distribution of education facilities is one of the most essential things to realizing the national education goals. Sumedang Regency is one of the places that distribution of Senior High School facilities are unequal in every sub. Purpose of this research are to analyze availability, distribution patterns and the range of Senior High School facility services in Sumedang Regency. The method for this research are using quantitative descriptive with analysis of fulfillment of the needs in every sub and demand of student in every Senior High School facilities also Geographic Information System (GIS) analysis using nearest neighbor and buffer. The results are availbility of Senior High School facilities in Sumedang Regency cannot accommodate the requirement of many students, because not able to fulfill at least 80% of students in every sub. The gap of students are not even, with 10 Senior High School only have less then 80% of students and 1 School had more then 110% of students. The pattern of senior high school facilities outfall using nearest neighbor analysis are clustered with p-value 0,003 dan z-score -2,95. Service range of Senior High School facilities using buffer analysis based on SNI 03-1733-2004 may be known that the senior high school facility service could not serve the entire student population because they only reach 54.97% student population in Sumedang Regency.